An open trial of individualized face-to-face cognitive behavior therapy for psychological distress in parents of children after end of treatment for childhood cancer including a cognitive behavioral conceptualization - Ljungman, Lisa (PeerJ, 2018)
OBJECTIVE: A subgroup of parents of children who have been treated for childhood cancer report high levels of psychological distress. To date there is no empirically supported psychological treatment targeting cancer-related psychological distress in this population. The aim of the current study was to test the feasibility and preliminarily evaluate the effect of individualized face-to-face cognitive behavior therapy (CBT) for parents of children after the end of treatment for childhood cancer. A secondary aim was to present a cognitive behavioral conceptualization of cancer-related distress for these parents. METHODS: An open trial was conducted where 15 parents of children who had completed successful treatment for cancer three months to five years earlier and who reported psychological distress related to a child’s previous cancer disease were provided CBT at a maximum of 15 sessions. Participants were assessed at baseline, post-intervention, and three-month follow-up using self-reported psychological distress (including posttraumatic stress symptoms (PTSS), depression, and anxiety) and the diagnostic Mini-International Neuropsychiatric Interview. Feasibility outcomes relating to recruitment, data collection, and delivery of the treatment were also examined. Individual case formulations for each participant guided the intervention and these were aggregated and presented in a conceptualization detailing core symptoms and their suggested maintenance mechanisms. RESULTS: A total of 93% of the participants completed the treatment and all of them completed the follow-up assessment. From baseline to post-assessment, parents reported significant improvements in PTSS, depression, and anxiety with medium to large effect sizes (Cohen’s d = 0.65–0.92). Results were maintained or improved at a three-month follow-up. At baseline, seven (47%) participants fulfilled the diagnostic criteria for major depressive disorder and four (29%) fulfilled the criteria for posttraumatic stress disorder, compared to none at a post-assessment and a follow-up assessment. The resulting cognitive behavioral conceptualization suggests traumatic stress and depression as the core features of distress, and avoidance and inactivity is suggested as the core maintenance mechanisms. CONCLUSION: The treatment was feasible and acceptable to the participants. Significant improvements in distress were observed during the study. Overall, results suggest that the psychological treatment for parents of children after end of treatment for childhood cancer used in the current study is promising and should be tested and evaluated in future studies.